Sistema de información web en donde se centralizará los datos de las mascotas perdidas, encontradas o recuperadas en el departamento de Cundinamarca - LostPet (2021)
In the department of Cundinamarca there is currently no site where the information on found or lost dogs or cats is centralized, thus making the search process for the pet longer. The LostPET project seeks to help improve this search taking into account that a pet becomes part of the family, turning its loss into a difficult moment that perhaps some unscrupulous people want to take advantage of to take advantage of, which is why LostPET protects the personal data of users.